PENGARUH SELF REGULATED LEARNING TERHADAP ACADEMIC BURNOUT PESERTA DIDIK - Pratiwi, Nabilla Fujias; Astuti, Indri; Fergina, Ana (Universitas Tanjungpura, 2023)
Learning can take place anywhere, for example through formal or informal education. Learners in formal education must adapt to the learning activities undertaken and be able to self-regulate their learning. However, each student's learning activities do not go well due to fatigue. Therefore, the researchers wanted to know the impact of self-regulated learning on the learning saturation level of Grade VIII SMP Negeri 3 Sungai Raya students. The purpose of this study was to collect information and describe the impact of self-regulated learning on academic burnout among students of Grade VIII SMP Negeri 3 Sungai Raya. This study uses a quantitative descriptive method. The population of this study consisted of 224 Grade VIII students at SMP Negeri 3 Sungai Raya, with a sample size of 76 respondents. The data collection tool is a questionnaire. Research results show that the ability to self-regulate learning of Grade VIII students is 74% at the